La finance éthique et la crise de 2008 : l’exemple britannique - Aymen Boughanmi (Revue Française de Civilisation Britannique)
Since 2008, ethical finance has emerged as a promising answer for the supposedly moral deficit of the financial sector. However, the hopes that such solution inspired raise many questions about this specific evolution of the capitalist system and the nature of its ideological innovations. In this context, United Kingdom represents a significant case. As its financial market offers a welcoming framework for conflicting forms of ethical finance, it seems important to study the different articulations of their founding principles, as well as their ideological and practical implications in a context of an economic crisis.